2020
DOI: 10.1177/1362361320926070
|View full text |Cite
|
Sign up to set email alerts
|

The health of college students on the autism spectrum as compared to their neurotypical peers

Abstract: Data from an online survey of undergraduate students at 14 colleges and universities were used to estimate the association of autism with six physical and mental health outcomes, accounting for comorbidity with other disabilities (learning disability, attention deficit hyperactivity disorder, sensory impairment, mobility impairment, mental health disorder, or other disabilities). Autism status was determined based on registration for disability accommodations based on autism and/or self-reports of an autism di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Several studies taken from both clinical and general population samples (with sample sizes ranging from 89 to 4123 autistic participants) suggest that autistic individuals are less likely to smoke, use tobacco, use nicotine, 11 , 12 , 13 or misuse substances (including alcohol) than non-autistic individuals. 12 , 13 , 14 , 15 , 16 By contrast, results from larger studies and one systematic review indicate that autistic individuals might have an increased likelihood of developing substance use-related problems. 17 , 18 , 19 , 20 Specifically, in large population-based studies in Sweden (including 26 986 autistic individuals) and Norway (including 7528 autistic individuals), autistic individuals were twice as likely to have substance use problems than non-autistic individuals; and even their non-autistic siblings and parents were at increased risk of substance use problems compared with controls, suggesting that genetic or environmental factors might contribute to risks.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies taken from both clinical and general population samples (with sample sizes ranging from 89 to 4123 autistic participants) suggest that autistic individuals are less likely to smoke, use tobacco, use nicotine, 11 , 12 , 13 or misuse substances (including alcohol) than non-autistic individuals. 12 , 13 , 14 , 15 , 16 By contrast, results from larger studies and one systematic review indicate that autistic individuals might have an increased likelihood of developing substance use-related problems. 17 , 18 , 19 , 20 Specifically, in large population-based studies in Sweden (including 26 986 autistic individuals) and Norway (including 7528 autistic individuals), autistic individuals were twice as likely to have substance use problems than non-autistic individuals; and even their non-autistic siblings and parents were at increased risk of substance use problems compared with controls, suggesting that genetic or environmental factors might contribute to risks.…”
Section: Introductionmentioning
confidence: 97%
“…These include situational factors such as physical health, employment, and family responsibilities, institutional factors such as policy, support programs, financial aid, and staff responsiveness, and dispositional factors such as self-confidence, attitudes, and beliefs [10,11]. Early identification of students at risk of dropping out during the first year of college can lead to early intervention actions such as tutoring, counseling, and mentoring, all of which prevent student withdrawal [12][13][14][15][16][17].…”
Section: Students With Autism Spectrum Disorders and Their First Year College Experiencesmentioning
confidence: 99%
“…Risk for mental health concerns in children who have autism is high (Kerns et al, 2020) and does not abate in the transition years. Studies in this special issue showed that physical and mental health were worse in autistic college students than in neurotypical peers (McLeod et al, 2021). Autistic transition-age youth also showed the highest use of mental health services and psychotropic medications relative to neurotypical peers or peers with attention deficit hyperactivity disorder (ADHD) or with diabetes mellitus (Ames, Massolo, Davignon, Qian, and Croen, 2021).…”
Section: Theme 3: Physical Health Needs Increase As Autistic People Transition To Adulthood But Often Are Ignoredmentioning
confidence: 99%